P047: Test characteristics of point of care ultrasound for the diagnosis of retinal detachment in the emergency department. (15th May 2017) - Docherty, G.; Francispragasam, M.; Silver, B.; Prager, R.; Maberley, D.; Lee, D.; Kim, D.J.; Albiani, D.; Kirker, A.; Andrew, M.
Abstract : Introduction: The acute onset of flashes and floaters is a common presentation to the emergency department (ED). The most emergent etiology is retinal detachment (RD), which requires prompt ophthalmologic assessment. Previous studies of point of care ultrasound (POCUS) have reported high sensitivity and specificity for RD, but are limited by small sample size, use of highly trained and experienced sonographers, and referral bias. Our primary objective was to assess the test characteristics of POCUS performed by a large heterogeneous group of emergency physicians (EPs) for the diagnosis of RD.Methods: This was a prospective diagnostic test assessment of POCUS performed by EPs with varying ultrasound experience on a convenience sample of ED patients presenting with the complaint of flashes or floaters in one or both eyes. Participating EPs completed a one hour didactic lecture and were expected to demonstrate appropriate performance of one practice scan before enrolling patients. After standard ED assessment, patients underwent an ocular POCUS scan targeted to detect RD. EPs recorded the presence or absence of RD on the data collection instrument based on their POCUS scan. After completing their ED visit, all patients were assessed by a retina specialist who was blinded to the results of the POCUS scan. We calculated sensitivity and specificity with associated exact binomial confidence intervals (CI) using the retina specialist's determination of the final diagnosis as the criterion standard.Results: A total of 30 EPs, consisting of 21 staff physicians and 9 residents, participated in this study. These EPs performed a total of 128 POCUS scans. Of these scans, 13 were excluded. Of the remaining 115 enrolled patients, median age was 60 years, and 64% were female. The retina specialist diagnosed RD in 16 (14%) cases. The sensitivity and specificity of POCUS for detecting RD was 75% (95% CI 48% to 93%) and 94% (95% CI 87% to 98%), respectively. The positive likelihood ratio was 12.4 (95% CI 5.4 to 28.3), and negative likelihood ratio was 0.27 (95% CI 0.11 to 0.62).Conclusion: In a heterogeneous group of EPs with varying ultrasound experience, POCUS demonstrates high specificity but only intermediate sensitivity for the detection of RD. A negative POCUS scan is not sufficiently sensitive to rule out RD in a patient with new onset flashes or floaters.